2002
DOI: 10.1016/s1097-2765(02)00490-2
|View full text |Cite
|
Sign up to set email alerts
|

Activator-Specific Recruitment of TFIID and Regulation of Ribosomal Protein Genes in Yeast

Abstract: In yeast, TFIID strongly associates with nearly all ribosomal protein (RP) promoters, but a TAF-independent form of TBP preferentially associates with other active promoters. RP promoters are regulated in response to growth stimuli, in most cases by a Rap1-containing activator. This Rap1-dependent activator is necessary and sufficient for TFIID recruitment, whereas other activators do not efficiently recruit TFIID. TAFs are recruited to RP promoters even when TBP and other general transcription factors are not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
155
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(182 citation statements)
references
References 45 publications
25
155
1
1
Order By: Relevance
“…In contrast, promoters with lower activities have, on average, Rap1 sites that are located ;60 bp further upstream compared with their location in the highactivity promoters, and are followed by a region with high nucleosome affinity. Rap1 is clearly critical for RP transcription, since deleting its sites ( Woudt et al 1986;Mencia et al 2002;Zhao et al 2006), and even changing the orientation of its sites (Woudt et al 1986) in RP promoters significantly reduces RP transcription. Our finding of different organizations of Rap1 sites between promoters with high and low activities further suggests that its contribution to transcription depends on its exact organization within the promoter, but it is unclear whether the effect depends on the exact location of the Rap1 site and/or on the presence of the nucleosome between the Rap1 site and the transcription start site.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In contrast, promoters with lower activities have, on average, Rap1 sites that are located ;60 bp further upstream compared with their location in the highactivity promoters, and are followed by a region with high nucleosome affinity. Rap1 is clearly critical for RP transcription, since deleting its sites ( Woudt et al 1986;Mencia et al 2002;Zhao et al 2006), and even changing the orientation of its sites (Woudt et al 1986) in RP promoters significantly reduces RP transcription. Our finding of different organizations of Rap1 sites between promoters with high and low activities further suggests that its contribution to transcription depends on its exact organization within the promoter, but it is unclear whether the effect depends on the exact location of the Rap1 site and/or on the presence of the nucleosome between the Rap1 site and the transcription start site.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These experiments indicate that a mechanism for enhancer-promoter specificity is the differential recruitment of TAFs by the enhancers. In related studies, it was found that a Rap1-containing activator recruits TFIID to ribosomal protein (RP) promoters, which generally lack canonical TATA box motifs (Mencía et al 2002). This Rap1-containing activator also stimulates transcription that is directed by the his3 T C element (which, as noted above, does not have a canonical TATA sequence) but not by the canonical T R TATA box.…”
Section: Tata 1 Versus Tatamentioning
confidence: 90%
“…Only a small percentage of promoters seem to be exclusively SAGA-or TFIID-dependent in vivo (Lee et al 2000). In general, the requirement of a particular promoter for SAGA or TFIID is determined by the core promoter sequence, and the particular activator determines whether SAGA or TFIID is recruited to a promoter (Shen and Green 1997;Cheng et al 2002;Mencia et al 2002). It seems that many yeast promoters can use either SAGA or TFIID, because a double mutation of SAGA and TFIID subunits or a mutation of a shared TFIID/SAGA subunit affects expression from many more yeast genes than does a single mutation of either TFIID or SAGA specific subunits (Lee et al 2000).…”
mentioning
confidence: 99%